Temporal associations between individual changes in hormones, training motivation and physical performance in elite and non-elite trained men - BT Crewther; J Carruthers; LP Kilduff; CE Sanctuary; CJ Cook (Biology of Sport, 2016)
To advance our understanding of the hormonal contribution to athletic performance, we examined the temporal associations between individual changes in testosterone (T) and/or cortisol (C) concentrations, training motivation and physical performance in elite and non-elite trained men. Two male cohorts classified as elites (n = 12) and non-elites (n = 12) completed five testing sessions over a six-week period. The athletes were tested for salivary T, C, T/C ratio, self-perceived training motivation, countermovement jump (CMJ) height and isometric mid-thigh pull peak force (IMTP PF), after which an actual training workout was performed. The elite men reported higher motivation to train and they produced greater CMJ height overall, whereas the non-elites had higher pooled T levels (p < 0.05). No significant group differences in C concentrations, T/C ratio or IMTP PF were found. The individual changes in T levels were positively associated with training motivation in the elite men only (p = 0.033), but the hormonal and motivation measures did not predict CMJ height or IMTP PF in either group. The monitoring of elite and non-elite men across a short training block revealed differences in T levels, motivation and lower-body power, which may reflect training and competitive factors in each group. Despite having lower T levels, the elite athletes showed better linkage between pre-training T fluctuations and subsequent motivation to train. The nature of the performance tests (i.e. single repetition trials) could partly explain the lack of an association with the hormonal and motivational measures.